КАЙНОЗОЙН СЭВСГЭР ХУРДСЫН ЗУЗААНЫГ ҮНЭЛЭХ ГРАВИХАЙГУУЛЫН НЭГ ХЭМЖЭЭСТ ЗАГВАР - Н.Арвисбаатар; Б.Ганбат (Geological Issues, 2023)
КАЙНОЗОЙН СЭВСГЭР ХУРДСЫН ЗУЗААНЫГ ҮНЭЛЭХ ГРАВИХАЙГУУЛЫН НЭГ ХЭМЖЭЭСТ ЗАГВАР